Microbial oxidation of medium chain fatty alcohol in the synthesis of sophorolipids by candida bombicola and its physicochemical characterization - Pulate, Vrushali Dengle; Bhagwat, Sunil S.; Prabhune, Asmita Ashutosh (Journal of Surfactants and Detergents, 2013)
Sophorolipids (SL) are glycolipid biosurfactants abundantly produced from different feedstocks by yeasts and have been widely developed for various applications. The amphipathic structures of sophorolipids imparts to them surfactant type properties. These biosurfactants are readily isolated in high yield and are nontoxic and biodegradable, which make them industrially interesting as surfactants or emulsifiers. Sophorolipid production was carried out using glucose as a hydrophilic source and lauryl alcohol C12-14, as a hydrophobic source by Candida bombicola (ATCC 22214). Process economics and environmental attractiveness was increased by using a low cost substrate. Optimization studies were carried out where the effect of glucose concentration, pH, temperature and metal ions on sophorolipid production was studied. Optimum production of sophorolipid obtained using lauryl alcohol (SLLA) was achieved after 96 h, the initial pH of the medium was 6.0 with 10 % glucose at 30 A degrees C. Primary characterization of SLLA was done by FTIR. The SLLA showed high physicochemical properties in terms of the surface activities when compared with synthetic surfactants including dodecyl tetraethylene glycol ether and sodium lauryl sulfate. The surface tension of SLLA thus obtained was found to be 24 mN/m with a critical micellar concentration (CMC) value of 0.68 mg/L. Antimicrobial testing showed that SLLA have potent antimicrobial activity against both gram negative bacteria, Escherichia coli (ATCC 8739) and gram positive cocci, Staphylococcus aureuss (ATCC 2079).
Keywords: Biosurfactants; Candida bombicola; CMC; Lauryl alcohol C12-14; sophorolipids; Surface tension

Antimicrobial and SEM studies of sophorolipids synthesized using lauryl alcohol - Dengle-Pulate, Vrushali; Chandorkar, Parul; Bhagwat, Sunil S.; Prabhune, Asmita Ashutosh (Journal of Surfactants and Detergents, 2014)
In recent years, researchers have developed biosurfactants for industrial, pharmaceutical and medical applications revealing the promising biological activities of these biomolecules. One of the best studied microbial surfactants are glycolipids, especially sophorolipids (SLs) produced by selected non-pathogenic yeast species of Candida. They are biodegradable, non-toxic and are environmentally friendly. Sophorolipid production was carried out using glucose as the hydrophilic source and lauryl alcohol C12-14, as the hydrophobic source using Candida bombicola ATCC 22214. Primary characterization of the SL obtained using lauryl alcohol (SLLA) was done by FTIR which depicted the presence of alkyl sophorosides/SLs. Antimicrobial activity testing revealed that SLLA showed complete inhibition against gram negative bacteria, Escherichia coli (ATCC 8739) Pseudomonas aeruginosa (ATCC 9027) at 30 and 1 mu g/ml at a contact time of 2 and 4 h respectively. Whereas for gram positive bacteria Staphylococcus aureus (ATCC 6358), Bacillus subtilis (ATCC 6633), complete inhibition was observed at 6 and 1 mu g/ml respectively at a contact time of 4 h. The formed SLLA showed noteworthy inhibition against the pathogenic yeast Candida albicans (ATCC 2091) at 50 mu g/ml with a contact time of 4 h. These values are remarkably low compared to reported values of oleic acid SLs and linolenic acid SLs which were studied for antimicrobial properties. Scanning electron microscopy analysis of the treated cells revealed the changes in morphology and topography of the microorganisms.
Keywords: Antimicrobial property; Biosurfactants; Candida bombicola; Lauryl alcohol; sophorolipids